Parasocial interactions and digital characters: the changing landscape of cinema and viewer/character relationships. Issue 1 (1st January 2021) - Sheldon, Zachary; Romanowski, Max; Shafer, Daniel M.
ABSTRACT: This study investigates whether parasocial interactions (PSIs) vary in strength depending on whether a character is created entirely through computer-generated imagery (CG), a hybrid character enhanced by CGI, or real, portrayed by a real human actor. One-hundred and forty-four participants watched a randomly selected film narrative from the three conditions, and strength of PSIs was measured. Results indicate that PSIs formed with hybrid CGI characters are just as strong as those formed with non-CGI characters. Audience members formed stronger PSIs with both natural and hybrid characters than they did with all-CGI characters. This finding suggests that movie viewers relate to characters enhanced by CGI just as effectively as they relate to entirely human characters. All-CGI characters may not be as relatable, but this may be due to the types of characters, typically non-humans, that are usually created entirely with CGI rather than failings of the technology itself.